A influência da propriedade estatal no desempenho das empresas no mercado de capitais brasileiro - Santos, Leandro da Costa (2019)
The literature on Ownership structure documents that the performance of companies is affected by the profile of their controlling shareholders, which may significantly influence the search for the company goals based on their preferences. In such context, the State emerges as an integral part of the Ownership structure of the companies, with its own public policy objectives, generally directed to the search for public value. Therefore, based on the theories of Property rights, Transaction Cost and Agency, which combined provided a more precise view on this dynamic topic, that this research came to fruition with the objective of analyzing the impact of State-Owned on the performance of firms. The analysis was carried out through hypothesis testing of the relation between State-Owned and the performance of the companies as represented by the Net Added Value divided by the total revenue (VALPR). The statistical relation was analyzed via Pooled Ordinary Least Squared regression, and as an empirical complement, quantile regression was used. The Pooled OLS and Quantile results converged and supported each other, evidencing that State property holds a positive and significant relation with the performance of the companies analyzed, thus contributing to the improvement of the Net added value produced by those entities up to a certain point. The main contribution of the study was to demonstrate empirically the influence of State-Owned on the performance of companies and to bring State property into the theoretical debate.